Case Report pada Primigravida Trimester II dengan Masalah Kurang Energi Kronik (KEK) di Wilayah Kerja Puskesmas Kamal Kabupaten Bangkalan - Leonita Krisantie Putri, Angel; Wayanti, Sri; Anisak, Siti (Sinar : Jurnal Kebidanan, 2026)
Background: Chronic Energy Deficiency (CED) is a condition caused by inadequate intake of energy and protein, resulting in insufficient nutritional fulfillment for the body. Nutritional adequacy in pregnant women is indicated by a Mid-Upper Arm Circumference (MUAC) >23.5 cm or a Body Mass Index (BMI) >18.5 kg/m². Continuous monitoring and comprehensive midwifery care are essential for early detection and management of potential complications. Purpose: This study aimed to identify subjective and objective findings, analyze data, provide appropriate care, and evaluate outcomes for a pregnant woman with CED. Methods:  This research employed a case study design focusing on a single patient, Mrs. “W”, G1P0A0, at 28–29 weeks of gestation, diagnosed with CED. The care process consisted of three home visits conducted in Banyu Ajuh Village during June 2025. Inclusion criteria included primigravida in the second trimester with CED, aged 20–35 years, free from infectious diseases, able to communicate, and literate. Data were obtained through anamnesis, physical examination, review of the Maternal and Child Health (MCH) handbook, data analysis, midwifery management, and evaluation. Results: During the first visit, the patient was diagnosed with CED, presented with fatigue, and had a MUAC below 23.5 cm. The care included nutritional counseling, iron and multiple micronutrient supplementation, and education on pregnancy danger signs. Although weight gain was observed, CED persisted. Fatigue resolved by the second visit, and back pain experienced afterward subsided during the third visit. Conclusion: Midwifery care was provided according to appropriate standards. Despite several discomforts, they were effectively managed. Midwives are advised to continue integrated antenatal care, provide nutritional support, ensure compliance with iron supplementation, and encourage regular check-ups, particularly for women with a history of CED